Comparison of Hematological and Inflammatory Markers to Predict Outcome in Covid-19 in 1st and 4th Wave - Khan, Khalid; khan, Hamzullah; khan, Shahtaj; Fawad Khan, Mohammad; Ali, Mohammad; Usman, Mohammad (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: To compare the values of the hematological and inflammatory markers in 1st and 4th waves to predict the outcome of COVID-19 in a hospital-based study. METHODOLOGY: This comparative study was conducted in the Department of Hematology, Hayatabad Medical Complex Peshawar, from April 2020 to 20 August 2021. Tests of significance (Independent t-test/Mann Whitney U test) and Chi-square test were used. Relevant information was recorded on a pre-designed proforma prepared following the study’s objectives. RESULTS: A total of 178 patients, 71 from (the 1st wave) and 107 from (the 4th wave) with known outcomes, were studied. A statistically significant difference exists between the groups (1st vs 4th wave) regarding hematological markers; neutrophil to lymphocyte ratio (NLR) (p=0.02), Absolute Neutrophilic count (ANC) (p=0.01) and platelet count (p=0.001). Similarly, significantly higher inflammatory markers values were recorded in the 1st wave compared with the 4th wave regarding inflammatory markers; CRP (p=0.002) and D-dimer (p=0.001). During the 1st wave, Total Leukocyte Count (TLC), ANC and d-dimer were the leading prognostic indicators to predict mortality/worst outcome in COVID-19 with an Area Under Curve (AUC) of 0.74, 0.70 and 0.7 on receiver operating characteristics (ROC) respectively. In 4th, the Area under the curve (AUC) of d-dimer was 0.84 to predict mortality. CONCLUSION: TLC, ANC, NLR, and low platelet count were the worst hematological markers in COVID-19 in the first wave, while d-dimer and CRP were the primary prognostic inflammatory markers. Unlikely in the 4th wave, the prognostic values of hematological markers were merely significant. The d-dimer values in both the waves proved to be reliable for predicting the severity and mortality of COVID-19.